A MODEL OF UNIVERSITY EXAMINATION MONITORING SYSTEM - Henry, Ogbu Nwani (IJRDO -Journal of Computer Science Engineering, 2016)
This work takes into consideration thesystem of examination invigilation in Nigeriauniversities. Over the years, the extent ofstudents’ malpractice in examinations andthe resultant effects when confronted byinvigilators or university security agents havebeen on the increase and devastating.According to Ejiogu (2001), general moraldecadence and the high premium placed onachievement and certificates by Nigerianshas in recent times spawned examinationfraud. There arose the need for anexamination automated monitoring systemthat will handle this societal menace. Thisjournal therefore x-rays the exact waystudents take examination and tries to portrayeach student’s grade with his academiccapabilities. It is a system of examinationconduction that monitors the examinationarena (halls) and stores live-fed videoedscenario for future screening and use. Thesystem is designed and developed withwebcams at the examination halls to capturethe student’s face, posture and movement atevery moment during examination. The